Maintaining ideological security and legitimacy in digital China: Governance of cyber historical nihilism - Xu, Jian; Gong, Qian; Yin, Wen (SAGE, 2022)
This article studies the governance of ‘cyber historical nihilism’ in China. By performing document analysis of the regulatory policies and actions against cyber historical nihilism, we found that cyber historical nihilism is mainly governed as harmful ‘online content’ and a threatening ‘ideological trend’, and its governance has incorporated agencies and measures of China’s ‘internet governance’ and ‘ideological and political education’. We argue that cyber historical nihilism has been securitised by the Chinese Communist Party as an urgent threat to the nation’s ideological and political securities. The governance of cyber historical nihilism aims to maintain the Chinese Communist Party’s authority in history writing and its legitimacy and longevity as the ruling party. The Chinese Communist Party’s emphasis and intensity in governing cyber historical nihilism has not only demonstrated the ideological turn to Maoism in internet governance, propaganda and politics under Xi Jinping’s leadership, but also the Chinese Communist Party’s ability and resilience to adapt to new challenges in the ideological field in the digital age.